Жирова основа для крем-мила з лікувально-профілактичними властивостями - Кричковська, Лідія Василівна; Марченко, Валерія Сергіївна (НТУ "ХПІ", 2015)
В статті вивчалась проблема недостатності біологічно активних речовин в ліпідному складі епідермісу сухої шкіри. Проведено аналіз підвищення біологічної цінності олій за рахунок їх купажування. Науково обґрунтовано та розроблено склад купажованої олії – жирової основи, що представляє собою олію підвищеної біологічної цінності, збалансовану за складом ПНЖК ω–3 та ω–6 груп, для крему-мила з лікувально-профілактичними властивостями.

Object of study is a cosmetic soap formulation with balanced polyunsaturated fatty acids of the fat phase, rich in antioxidants. The purpose of this study is to develop a scientific basis and formulation of cosmetic soap, enriched with polyunsaturated fatty acids ω-3 group and resistant to oxidative damage by antioxidants. The present study compares technical characteristics and biological activities of oils and oil blends of three species. The soya bean oil shows the ratio of ω-6/ω-3 PUFAs that satisfies the requirements for the rational PUFAs composition in food stuffs and cosmetics (6,4:1). The corn oil examples have the ratio 483:1, and the grape seed oil – 236:1 (linolenic acid is virtually not detected). The composition of antioxidants in the test oils was detected. The highest content of tocopherols among selected samples of oils has the corn oil. The mass fraction of vegetable oils in the oil blend is calculated from the need to obtain a predetermined ratio of PUFAs: ω-6:ω-3 = (9–10):1. In result a cosmetic product includes a vegetable oil blend having 70 % soya bean oil, 25 % corn oil, 5 % grape seed oil and including 67,8±1,0 % UFA, 58,9±1,0 % of which are PUFAs. The vegetable oil blend can be used alone or in combination with other ingredients. The vegetable oil blend moisturizes human skin, provides a protective barrier to dirt and weather, acts as an emollient, and may promote healing of cracked, dry or otherwise damaged skin.
Fatty basis for liquid soap cream with curative properties
Keywords: купажовані олії; поліненасичені жирні кислоти; косметичні засоби; окиснення; антиоксиданти; antioxidant; blended oil; cosmetic cream